INTEGRATION OF DROUGHT DISASTER MITIGATION AND FOOD SECURITY IN SOCIAL STUDIES EDUCATION THROUGH BREADFRUIT TREE PLANTING IN KUANGSAN VILLAGE, REMBANG REGENCY - Zulfa, Safira; Falaq, Yusuf (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
Kuangsan Village, located in Kaliori District, Rembang Regency, is one of the areas frequently affected by drought due to declining rainfall and limited water resources. This condition directly reduces agricultural productivity and weakens local food security. As an initial mitigation and community empowerment effort, hundreds of breadfruit (Artocarpus altilis) seedlings were planted along riverbanks and drylands through collaboration among the Kaliori Military Subdistrict Command (Koramil), the village government, and local residents. This study aims to integrate drought mitigation activities and food security concepts into Social Studies (IPS) education based on environmental awareness and local wisdom. Using a descriptive qualitative method with a participatory approach, the research involved field observations, interviews with six key informants, and documentation of the seedling-planting activities. The early findings show that the breadfruit planting initiative has strong potential to support local food diversification in the future and can immediately serve as a contextual learning resource in Social Studies education. The activity enables students to understand human–environment interactions while strengthening cooperation, social responsibility, and ecological awareness. The study’s novelty lies in offering an early-stage transdisciplinary integration model between Social Studies education and disaster mitigation, positioning the breadfruit planting initiative as an educational entry point for building social and environmental resilience in rural communities.